Update on human papilloma virus - part I: epidemiology, pathogenesis, and clinical spectrum,, - Geraldo Magela Magalhães; Érica Cristina Vieira; Lucas Campos Garcia; Maria de Lourdes Ribeiro De Carvalho-Leite; Antônio Carlos Martins Guedes; Marcelo Grossi Araújo (Sociedade Brasileira de Dermatologia, 2021)
Abstract Infection with human papilloma virus (HPV) is related to a great number of cutaneous and mucosal manifestations. The spectrum of HPV ranges from inapparent infections, through various clinical benign presentations including cutaneous and mucosal disease, to malignant and premalignant conditions. New HPV types are currently described in the literature; many of them are characterized as high-risk types due to their oncogenic potential. Knowledge regarding their epidemiology and pathogenesis is important to understand not only infection and disease processes, but also to formulate the clinical and laboratory basis for diagnosis, therapeutics, and prophylactic measures. This non-systematic review aims to discuss and to update those aspects, with an emphasis on relevant topics for dermatologists. HPV infection and related diseases in the Brazilian scenario are highlighted, including common dermatologic conditions seen at clinics as well as the condition of a public health problem as a sexually transmitted infection. The oncogenicity of the virus and the variety of clinical outcomes - especially in the immunocompromised individuals - are addressed.